Reconceptualising public acceptability: A study of the ways people respond to policies aimed to reduce alcohol consumption. (May 2016) - Cohn, Simon
The issue of public acceptability of health policies is key if they are to have significant and lasting impact. This study, based on focus groups conducted in England, examines the ways people responded to, and made sense of, policy ideas aimed at reducing alcohol consumption. Although effective policies were supported in the abstract, specific proposals were consistently rejected because they were not thought to map onto the fundamental causes of excessive drinking, which was not attributed to alcohol itself but instead its cultural context. Rather than being influenced by the credibility of evidence, or assessed according to likely gains set against possible losses, such responses were established dynamically as people interacted with others to make sense of the topic. This has significant implications for policy-makers, suggesting that existing beliefs and knowledge need to be taken into account as potentially productive rather than obstructive resources.